Soil fungal abundance and plant functional traits drive fertile island formation in global drylands. (25th October 2017) - Ochoa‐Hueso, Raúl; Eldridge, David J.; Delgado‐Baquerizo, Manuel; Soliveres, Santiago; Bowker, Matthew A.; Gross, Nicolas; Le Bagousse‐Pinguet, Yoann; Quero, José L.; García‐Gómez, Miguel; Valencia, Enrique; Arredondo, Tulio; Beinticinco, Laura; et al.
Abstract: Dryland vegetation is characterized by discrete plant patches that accumulate and capture soil resources under their canopies. These "fertile islands" are major drivers of dryland ecosystem structure and functioning, yet we lack an integrated understanding of the factors controlling their magnitude and variability at the global scale. We conducted a standardized field survey across 236 drylands from five continents. At each site, we measured the composition, diversity and cover of perennial plants. Fertile island effects were estimated at each site by comparing composite soil samples obtained under the canopy of the dominant plants and in open areas devoid of perennial vegetation. For each sample, we measured 15 soil variables (functions) associated with carbon, nitrogen and phosphorus cycling and used the relative interaction index to quantify the magnitude of the fertile island effect for each function. In 80 sites, we also measured fungal and bacterial abundance (quantitative PCR) and diversity (Illumina MiSeq). The most fertile islands, i.e. those where a higher number of functions were simultaneously enhanced, were found at lower elevation sites with greater soil pH values and sand content under semiarid climates, particularly at locations where the presence of tall woody species with a low‐specific leaf area increased fungal abundance beneath plant canopies, the main direct biotic controller of the fertile island effect in the drylands studied. Positive effects of fungal abundance were particularly associated with greater nutrient contents and microbial activity (soil extracellular enzymes) under plant canopies. Synthesis . Our results show that the formation of fertile islands in global drylands largely depends on: (1) local climatic, topographic and edaphic characteristics, (2) the structure and traits of local plant communities and (3) soil microbial communities. Our study also has broad implications for the management and restoration of dryland ecosystems worldwide, where woody plants are commonly used as nurse plants to enhance the establishment and survival of beneficiary species. Finally, our results suggest that forecasted increases in aridity may enhance the formation of fertile islands in drylands worldwide. Abstract : Our results show that the most fertile islands in global drylands are found at lower elevation sites with greater soil pH values and sand content under semiarid climates, particularly at locations where the presence of tall woody species with a low‐specific leaf area increased fungal abundance beneath plant canopies. Our study also has broad implications for the management and restoration of dryland ecosystems worldwide, where woody plants are commonly used as nurse plants to enhance the establishment and survival of beneficiary species. Finally, our results suggest that forecasted increases in aridity may enhance the formation of fertile islands in drylands worldwide.